Developmental patterning of peptide transcription in the central circadian clock in both sexes - Carmona-Alcocer, Vania; Brown, Lindsey S.; Anchan, Aiesha; Rohr, Kayla E.; Evans, Jennifer A. (Frontiers in Neuroscience, 2023)
Neuropeptide signaling modulates the function of central clock neurons in the suprachiasmatic nucleus (SCN) during development and adulthood. Arginine vasopressin (AVP) and vasoactive intestinal peptide (VIP) are expressed early in SCN development, but the precise timing of transcriptional onset has been difficult to establish due to age-related changes in the rhythmic expression of each peptide. To provide insight into spatial patterning of peptide transcription during SCN development, we used a transgenic approach to define the onset of Avp and Vip transcription. Avp-Cre or Vip-Cre males were crossed to Ai9+/+ females, producing offspring in which the fluorescent protein tdTomato (tdT) is expressed at the onset of Avp or Vip transcription. Spatial patterning of Avp-tdT and Vip-tdT expression was examined at critical developmental time points spanning mid-embryonic age to adulthood in both sexes. We find that Avp-tdT and Vip-tdT expression is initiated at different developmental time points in spatial subclusters of SCN neurons, with developmental patterning that differs by sex. These data suggest that SCN neurons can be distinguished into further subtypes based on the developmental patterning of neuropeptide expression, which may contribute to regional and/or sex differences in cellular function in adulthood.